METHODS OF EDUCATION THROUGH ART IN STUDENTS IN THE PROCESS OF MUSIC EDUCATION AND UPBRINGING - Madaminov Nasimjon Xoljurayevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Music art, like works of art, leads a person to high values of nobility, from an early age to the appearance of a strange tone and reverberation of sound. The child learns to a certain extent to hear and feel music when he is still a young man who does not know how to hold a pencil in his hands, read and draw. Often these initial impressions can play an important role in the formation of attitudes towards music in people. Therefore, in the main areas of reform of general education and vocational schools, issues of radical transformation of educational work in music and secondary schools were also advanced.